The Tilt of the Velocity Ellipsoid of Different Galactic Disk Populations - Sun, Weixiang; Shen, Han; Liu, Xiaowei (The Astrophysical journal, 2023)
The tilt of the velocity ellipsoid is a helpful tracer of the gravitational potential of the Milky Way. In this paper, we use nearly 140,000 red clump (RC) stars selected from LAMOST and Gaia to make a detailed analysis of the tilt of the velocity ellipsoid for various populations, as defined by stellar ages and chemical information, within 4.5 ≤ R ≤ 15.0 kpc and ∣ Z ∣ ≤ 3.0 kpc, respectively. The tilt angle of the velocity ellipsoid of the RC sample stars is accurately described as α = α 0 arctan ( Z / R ) with α 0 = (0.68 ± 0.05). This indicates the alignment of the velocity ellipsoid is between cylindrical and spherical, implying that any deviation from the spherical alignment of the velocity ellipsoid may be caused by the gravitational potential of the baryonic disk. The results of various populations suggest that α 0 displays an age and population dependence, with values α 0 = (0.72 ± 0.08) and α 0 = (0.64 ± 0.07) for the thin and thick disks, respectively, and α 0 displays a decreasing trend as age (and [ α /Fe]) increases, meaning that the velocity ellipsoids of the kinematically relaxed stars are mainly dominated by the gravitational potential of the baryonic disk. We determine the α 0 –R relation for various populations, finding that α 0 displays oscillations with R for the different populations. The oscillations in α 0 appear in both kinematically hot and cold populations, indicating that resonances with the Galactic bar are the most likely origin for these oscillations.